Clotting Enzyme Activity Derived from the Coelomocytes of the Sea Star, Asterias Forbesi - Marcum, J A; Levin, J; Prendergast, R A (Thrombosis and Haemostasis, 1984)
Clotting enzyme activity was detected in lysates prepared from the coelomocytes of Asterias forbesi following incubation with endotoxin-activated Limulus amebocyte lysate. This activity was not detected in the cell-free coelomic fluid. The enzymatic activity from the sea star lysate hydrolyzed the synthetic substrate S2222 but not S2238 or S2251, and polymerized partially purified Limulus clottable protein. The clotting enzyme activity was not detected following treatment of the sea star cell lysate with endotoxin or with the clotting enzyme from Limulus lysate. The enzymatic activity, generated in sea star cell lysate by the activated Limulus lysate, was inhibited by the addition of benzamidine; and its effect was suppressed with rabbit anti-sera directed against Asterias whole cell lysate, but not with anti-sera directed against the previously reported Sea Star Factor.
Keywords: Clotting enzyme activity; Asterias forbesi; Coelomocyte lysate